System Greeting In Sasak Community In Toya Village, Aikmel District - Azir, Abdul; Saputra, Ari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe; (1) the greeting system in the Toya village, (2) the function of greetings in the Toya village, (3) the factors that influence greetings in the Toya village. This research used qualitative descriptive method with data collection techniques was listening and note-taking technique, conversation technique, and observation. Presentation of analysis result is carried out used formal and informal method. Based on the results of the analysis, it was found that (1) forms of greeting to older people in family relationships, forms of greeting to the same age and forms of greeting to younger people. (2) The function of greeting was to pay attention to the person you are talking to and as a means of controlling interaction. (3) Facts that influence greetings are social status factors, educational factors, age factors and kinship factors.